E-Cadherin Downregulation is Mediated by Promoter Methylation in Canine Prostate Cancer - Fonseca-Alves, Carlos Eduardo; Kobayashi, Priscila Emiko; Leis-Filho, Antonio Fernando; Lainetti, Patricia de Faria; Grieco, Valeria; Kuasne, Hellen; Rogatto, Silvia Regina; Laufer-Amorim, Renee (Frontiers in Genetics, 2019)
E-cadherin is a transmembrane glycoprotein responsible for cell-to-cell adhesion, and its loss has been associated with metastasis development. Although E-cadherin downregulation was previously reported in canine prostate cancer (PC), the mechanism involved in this process is unclear. It is well established that dogs, besides humans, spontaneously develop PC with high frequency; therefore, canine PC is an interesting model to study human PC. In human PC, CDH1 methylation has been associated with E-cadherin downregulation. However, no previous studies have described the methylation pattern of CDH1 promoter in canine PC. Herein, we evaluated the E-cadherin protein and gene expression in canine PC compared to normal tissues. DNA methylation pattern was investigated as a regulatory mechanism of CDH1 silencing. Our cohort is composed of 20 normal prostates, 20 proliferative inflammatory atrophy (PIA) lesions, 20 PC, and 11 metastases from 60 dogs. The E-cadherin protein expression was assessed by immunohistochemistry and western blotting and gene expression by qPCR. Bisulfite- pyrosequencing assay was performed to investigate the CDH1 promoter methylation pattern. Membranous E-cadherin expression was observed in all prostatic tissues. A higher number of E-cadherin negative cells was detected more frequently in PC compared to normal and PIA samples. High-grade PC showed a diffuse membranous positive immunostaining. Furthermore, PC patients with a higher number of E-cadherin negative cells presented shorter survival time and higher Gleason scores. Western blotting and qPCR assays confirmed the immunohistochemical results, showing lower E-cadherin protein and gene expression levels in PC compared to normal samples. We identified CDH1 promoter hypermethylation in PIA and PC samples. An in vitro assay with two canine prostate cancer cells (PC1 and PC2 cell lines) was performed to confirm the methylation as a regulatory mechanism of E-cadherin expression. PC1 cell line presented CDH1 hypermethylation and after 5-Aza-dC treatment, a decreased CDH1 methylation and increased gene expression levels were observed. Positive E-cadherin cells were massively found in metastases (mean of 90.6%). In conclusion, low levels of E-cadherin protein, gene downregulation and CDH1 hypermethylation was detected in canine PC. However, in metastatic foci occur E-cadherin re-expression confirming its relevance in these processes.